The quotable Jung - Harris, Judith R. (Judith Rachel), 1953-; Woolfson, Tony (Princeton University Press, 2015)
"C. G. Jung (1875-1961) was a preeminent thinker of the modern era. In seeking to establish an interdisciplinary science of analytical psychology, he studied psychiatry, religion, mysticism, literature, physics, biology, education, and criminology. He introduced the concepts of extraversion and introversion, and terms such as complex, archetype, individuation, and the collective unconscious. He stressed the primacy of finding meaning in our lives. The Quotable Jung is the single most comprehensive collection of Jung quotations ever assembled. It is the essential introduction for anyone new to Jung and the Jungian tradition. It will also inspire those familiar with Jung to view him in an entirely new way. The Quotable Jung presents hundreds of the most representative selections from the vast array of Jung's books, essays, correspondence, lectures, seminars, and interviews, as well as the celebrated Red Book, in which Jung describes his own fearsome confrontation with the unconscious. Organized thematically, this collection covers such topics as the psyche, the symbolic life, dreams, the analytic process, good and evil, creativity, alchemical transformation, death and rebirth, the problem of the opposites, and more. The quotations are arranged so that the reader can follow the thread of Jung's thought on these topics while gaining an invaluable perspective on his writings as a whole. Succinct and accessible, The Quotable Jung also features a preface by Judith Harris and a detailed chronology of Jung's life and work. The single most comprehensive collection of Jung quotations ever assembled Features hundreds of quotes Covers such topics as the psyche, dreams, good and evil, death and rebirth, and more Includes a detailed chronology of Jung's life and work Serves as the ideal introduction to Jung and the Jungian tradition."